USULAN PENINGKATAN OVERALL EQUIPMENT EFFECTIVENESS PADA MESIN MOULDING DENGAN MEMINIMUMKAN SIX BIG LOSSES - sormin, firman okyadi; Zetli, sri (Computer Science and Industrial Engineering, 2020)
Production machinery and equipment are important elements in supporting the production sustainability of a manufacturing company. The machine becomes the main demand to continue to maintain and even improve the machine to remain optimal in producing goods and able to meet consumer demand. PT Cicor Panatec Batam is a company in Batam that manufactures beauty tools. some of the machines used, the Engel 200T, are injection molding machines, losses resulting from the production process caused by downtime that occur every day. The purpose of this study is to determine engine efficiency, six big losses which has the largest percentage of causes of engine performance decline, determine the low value of engine effectiveness from the factors and root causes of the problem, and make suggestions for improvement. In this study the determination of the value of the effectiveness of the machine using the OEE method and steps to correct the problem using FMEA. Obtained the OEE value calculation is 48.85%. In the Pareto diagram, the low value of the engine effectiveness is the breakdown losses with a value of 42.50%. Conduct identification using Ishikawa diagram to identify the cause of breakdown losses. The dominant problem causing failure is unstable heater heating with an RPN value of 140, and the smallest potential is damage to the mold RPN value of 90, proposed improvements to make SOPs, conduct periodic training, provide spare parts, and need to increase responsibility and care for care machine